IN VITRO EVALUATION OF PLANT EXTRACTS AND FUNGICIDES ON Ceratocystis fimbriata (ELLIS & HALST.), INCITANT OF POMEGRANATE WILT - RAJAT SHARMA; KISHORE KHOSLA (The Bioscan, 2020)
Wilt incited by Ceratocystis fimbriata is a major disease of pomegranate causing huge losses. Therefore, efforts were made to evaluate the efficacy of six plant extracts and eleven fungicides under in vitro conditions against test fungus. Among plant extracts, Nerium indicum was most effective giving 40.98 per cent mean growth inhibition of test fungus, followed by Adhatoda vasica (19.63%). Amongst systemic fungicides, carbendazim (Bavistin 50 WP), propiconazole (Tilt 25% EC) and hexaconazole (Contaf 5% EC) gave cent per cent mean growth inhibition of test fungus followed by fosetyl-Al (Aliette 80% WP) (58.39%). Non-systemic fungicides, mancozeb (Dithane M-45 75% WP) and propineb (Antracol 70% WP) were most effective with cent per cent mean growth inhibition of test fungus followed by copper oxy chloride (Blitox 50 WP) (75.67%) and captan (captan 50 WP) (55.55%). The combination of fungicides carbendazim 12%+ mancozeb 63% (Companion 75 WP) gave absolute (100%) inhibition of test fungus followed by captan 70%+ hexaconazole 5% WP (Taqat) and metiram+pyraclostrobin (Cabrio Top 60 WG) with mean per cent inhibition of 62.59 per cent and 45.67 per cent respectively. The plant extracts and fungicides varied in their inhibitory effect at different levels of concentrations.